E-flipbook innovation through problem-based learning: Enhancing mathematical concept mastery - Amirudin Amiruddin; Khoirunnisa Imama (CV. SPDFHarmony, 2025)
Background: Mathematical conceptual understanding remains a key issue in junior high school education. Innovation in learning media, such as digital tools, is needed to support effective learning. One promising approach is integrating Problem-Based Learning (PBL) with interactive digital media like E-flipbooks to enhance students’ engagement and comprehension in mathematics.Aim: This study aimed to develop a Problem-Based Learning-based E-flipbook that is valid, practical, and effective in improving students' mathematical concept understanding.Method: This research employed a Research and Development (R&D) design utilizing the ADDIE development model. The study participants were seventh-grade students from one of the public junior high schools located in the Batanghari Nuban sub-district during the 2024/2025 academic year. Data were collected through interviews, questionnaires, and mathematical concept comprehension tests. Data analysis involved expert validation, practicality indices, a proportion test, and a t-test.Results: The e-flipbook received high validity ratings from material experts (0.87) and media experts (0.90). Teacher and student responses indicated high practicality, with indices of 0.81 and 0.86, respectively. Additionally, over 60% of students demonstrated good understanding of mathematical concepts. The N-Gain and hypothesis test results showed a significant improvement in the experimental group compared to the control group.Conclusion: The e-flipbook developed through the problem-based learning approach was proven to be valid based on expert judgment, practical according to user responses, and effective in enhancing students’ mathematical concept understanding. These findings indicate that the integration of digital media and problem-based strategies can meaningfully support student learning. The product serves not only as a teaching aid but also as a tool to foster student engagement and active problem-solving. Therefore, this e-flipbook has the potential to be adopted as an innovative instructional resource in mathematics classrooms.